The Goldwyn Follies - Gershwin, George (Sound Image Enterprise, 1994)
Immortalized, sort of, in Harry Medved and Randy (Lowell) Dreyfuss's "The 50 Worst Films of All-Time", the big budget Technicolor musical hodgepodge "The Goldwyn Follies" (1938), like many of the films included in that book, actually isn't all that bad - there are far, far worse Hollywood musicals around - though the bare bones of a story holding it all together is awesomely idiotic. Though overlong and at times pretentious and uncultured, usually at the same time, 1938 audiences still probably enjoyed most of it well enough, though the lack of A-list stars, more than the film's shortcomings, probably doomed this very expensive production at the box office. But it does have a lot of talent behind it: George and Ira Gershwin wrote most of the songs, Ben Hecht (among many others) wrote the sometimes funny script, it was photographed by the great cinematographer Gregg Toland (three years before he shot Citizen Kane). [www.dvdtalk.com]